Empowering Mothers of Children with Special Needs in Early Childhood Inclusion - Bayrakli, Hatice; Sucuoglu, Bulbin (Anadolu Univ, 2018)
Parents of young children with special needs in inclusion are among key stakeholders influencing the effectiveness of inclusion. There is significant evidence to suggest, however, that difficulties they encounter throughout inclusion hinder parents to perform their role as partners. This suggests that their role in their child's education would be highly limited unless their needs resulting from the challenges they face are not met. Meeting their needs would empower them in fulfilling their roles and increase the success of inclusion. This study examines the development and evaluation of a needs-based training program designed for the mothers of children with special needs enrolled in inclusive preschools in North Cyprus. Aiming to support them in overcoming the difficulties they experience throughout inclusion by empowering them as partners, present study employs a mixed methods approach with a dominant qualitative strand. Findings of the study suggest the program have positive contributions to participating mothers and their children.
Keywords: Early childhood inclusion; mothers' needs; training program; collaboration; empowerment